Contributions of digital transformation as a strategic direction in improving the quality of Algerian university services - BENFOUGHAL, Ahlem; BADISSI, Fahima (Journal of Human Sciences, 2025)
In light of the dominance of modern technology and smart technology, digital transformation has become a strategic direction and an imperative necessity for countries and their governments seeking to develop their institutions and improve their services. This research paper attempts to shed light on the contributions of digital transformation to improving the quality of public services at Algerian universities through the innovation and development of digital public services aimed at improving the student experience, professor efficiency and employee performance and elevating Algerian universities to the ranks of international universities. To accomplish this study, a descriptive analytical approach was followed when addressing the theoretical framework of digital transformation, strategic direction, digital public services and then the challenges facing Algerian universities. The study concluded that digital transformation is the main pillar for improving the quality of Algerian university services and making higher education more comprehensive and innovative to support academic and research progress in a sustainable manner.